Analisa Faktor Kejadian Caregiver Burden Pada Keluarga Dengan Penyakit Kronis - Lintang Puspita Prabarini; Bima Aminul Karim; Sekarini (Jurnal Gema Keperawatan, 2026)
Chronic illness is a long-term condition that affects not only patients but also their families, who often serve as informal caregivers. Families caring for individuals with chronic illness frequently encounter complex challenges that contribute to caregiver burden. This study aimed to analyze the factors associated with caregiver burden among families of individuals with chronic illness using the Calgary Family Assessment Model (CFAM) and Family Health Assessment (FHA) approaches A cross-sectional study was conducted from November 2023 to January 2024 in Malang Regency, using accidental sampling. 120 respondents participated in the study. Caregiver burden was measured using an adapted version of the Burden Scale for Family Caregivers. Structural equation modeling–partial least squares (SEM-PLS) was employed to analyze the data. The majority of respondents were female (73,3%) and aged 26–33 years (36,7%), with most experiencing a moderate level of caregiver burden. The results revealed a significant negative relationship between contextual factors and caregiver burden (T-statistic = 3,854, p < 0,01). In contrast, functional factors (T-statistic = 2.751, p < 0.01) and structural factors (T-statistic = 3,078, p < 0,01) were positively and significantly associated with caregiver burden. These findings indicate that chronic illness affects not only patients but also family caregivers, with various contextual, functional, and structural factors contributing to the development of caregiver burden. Understanding these factors is essential for developing family-centered interventions aimed at reducing caregiver burden and improving family well-being.